Polyfaune. - Clermont, Albert; Delvigne, Catherine; Volant, Maria; Villa Myosotis, Dunkerque (Dunkerque : École des Beaux-Arts de Dunkerque, 2000)
Deblock, Sylvain ; Huh, Eun-Hee ; Jung, Ku-Eun ; Malinverno, Maryline ; Mally, Christelle ; Manteau, Marielle ; Nunne, Damien ; Petit, Antoine ; Potdevin, Dominique ; Rivollet, Anne ; Roussel, Stéphanie ; Samier, Carole ; Schmidt, Alexandre ; Villain, Benoit
Villa Myosotis, Dunkerque, du 12 au 26 mai 2000
kunstcatalogus